2020
DOI: 10.1016/j.jafrearsci.2020.103872
|View full text |Cite
|
Sign up to set email alerts
|

Archean tectonics in the sangmelima granite-greenstone terrains, Ntem Complex (NW Congo craton), southern Cameroon.

Abstract: Sangmelima granite-greenstone terrains (SGB) provide a new overview of the evolution of the Ntem Complex (South Cameroon), the northwestern part of the Congo Craton. The regional deformation is marked by a strong steep dips foliation and steeply plunging mineral-stretching. D 1 -related structures are folding and shearing by a D 2 deformation that is synchronous with extraction granitic dykes. D 1 -D 2 structures were developed during regional E-W sub-horizontal shortening under ductile conditions associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Nevertheless, some zircon grains show low Th/U ratio (< 0.1) and display homogenous textures, typical of metamorphic or anatectic zircons (e.g., Dong et al, 2017). Considering the partial reset of the U\ \Pb isotope system during the Neoarchean crustal anatexis (Akame et al, 2020), the upper intercept age of 2758 Ma of our high-K granite sample JA-1 (Fig. 7f) could probably represent the crystallization age of the rock.…”
Section: Interpretation Of Age Data 621 La-icp-ms U\ \Pb Zircon Agesmentioning
confidence: 88%
See 3 more Smart Citations
“…Nevertheless, some zircon grains show low Th/U ratio (< 0.1) and display homogenous textures, typical of metamorphic or anatectic zircons (e.g., Dong et al, 2017). Considering the partial reset of the U\ \Pb isotope system during the Neoarchean crustal anatexis (Akame et al, 2020), the upper intercept age of 2758 Ma of our high-K granite sample JA-1 (Fig. 7f) could probably represent the crystallization age of the rock.…”
Section: Interpretation Of Age Data 621 La-icp-ms U\ \Pb Zircon Agesmentioning
confidence: 88%
“…Johnson et al, 2018; reference therein). More recently Akame et al (2020) reported that the regional S 1 foliation (main structure of D 1 strain) were reworked by the D 2 deformation coeval with the second anatexis event materialized by melt migration along the C 2 shear zones and granitic dyke emplacement. Therefore, the age of 2744 ± 31 Ma is interpreted as the second stage of the anatexis coeval with the D 2 deformation event.…”
Section: Interpretation Of Age Data 621 La-icp-ms U\ \Pb Zircon Agesmentioning
confidence: 99%
See 2 more Smart Citations
“…These cratonic blocks have underwent multiple episodes of large-scale brittle deformation which created large discontinuities within them. Akame et al (2020Akame et al ( , 2021 documented the presence of large NW-SE, NE-SW and E-W trending brittle and ductile shear zones in the Ntem-Chaillu block, inherited from Neoarchean orogenesis. Similar deformation were also reported in the laterally equivalent Souanké Archean rocks in the Ivindo region (Gatsé Ebotehouna et al, 2021;Loemba et al, 2022).…”
Section: Regional Geology Of Western Africa and Continental Marginmentioning
confidence: 99%